TA CÓ: \(\left|x+1\right|=\frac{1}{2}\)
TH1: \(x+1=\frac{1}{2}\) TH2: \(x+1=\frac{-1}{2}\)
\(x=\frac{-1}{2}\) \(x=\frac{-3}{2}\)
THAY X =-1 /2 VÀO BIỂU THỨC M THAY X = -3/2 VÀO BIỂU THỨC M
\(M=5.\left(\frac{-1}{2}\right)^2-7.\frac{-1}{2}+\frac{1}{3}.\frac{-1}{2}-1\) \(M=5.\left(\frac{-3}{2}\right)^2-7.\frac{-3}{2}+\frac{1}{3}.\frac{-3}{2}-1\)
\(M=5.\frac{1}{4}-\frac{-1}{2}.\left(\frac{1}{3}+7\right)-1\) \(M=5.\frac{9}{4}-\frac{-3}{2}.\left(\frac{1}{3}+7\right)-1\)
\(M=\frac{5}{4}-\frac{-1}{2}.\frac{22}{3}-1\) \(M=\frac{45}{4}-\frac{-3}{2}.\frac{22}{3}-1\)
\(M=\frac{5}{4}-\frac{-11}{3}-1\) \(M=\frac{45}{4}-\left(-11\right)-1\)
\(M=\frac{47}{12}\) \(M=\frac{85}{4}\)
VẬY BIỂU THỨC M = 47/12 TẠI X= -1/2
................................= 85/4..............-3/2
CHÚC BN HỌC TỐT!!!!!!